Pendampingan Pencatatan Laporan Keuangan pada Usaha Ternak Ayam Potong Broiler - Saputra, Rian; Aprilia, Girlani; Nadia, Nona (EDUPEDIA Publisher, 2023)
This community service aims to strengthen the management of MSMEs in terms of implementing accounting so that the financial reports produced are in accordance with accounting principles. It is hoped that this PkM activity can support MSMEs in achieving good governance. In achieving good governance, MSMEs must apply accounting properly by presenting balance sheets and profit and loss reports. The method used in this PkM is Action Research in the form of assistance in recording financial reports in the boiler broiler chicken farming business which is carried out in Lepolima village, East Alok District. The results obtained from this activity are an understanding of recording financial reports in the form of balance sheets and profit and loss in the boiler broiler chicken farming business.